Understanding the investment behavior of FPIs and DIIs in Indian stock market in changing macroeconomic scenario: A post financial crisis (2008) analysis - Hani, Umme; Karimullah, Karimullah; Alam, Firoz (Edelweiss Applied Science and Technology, 2025)
Macroeconomic shocks and opportunities are considered to be a turning point of business decisions. This study seeks to examine the changing behaviour of institutional investors in Indian stock market in the changing macroeconomic scenario after global financial crisis (2008) for the period from 2008 to 2024. The study also provides a comparative analysis of domestic and foreign institutional investor’s investment behavior and examines the impact of macroeconomic shocks and opportunities on it. The macroeconomic shocks are proxy of the time period of global financial crisis and covid-19. The opportunities are measured by technological innovation, digital payment culture and stock market return. The institutional investors are classified broadly into two types, well known as Foreign Institutional Investors (FPIs) and Domestic Institutional Investors (DIIs). The trend and impact analysis are done by graphs and regression model. The impact of macroeconomic shocks and opportunities is measured by implying dummy variable Regression models and GARCH models. The finding suggests that the growth in purchase and sale of securities by DIIs is more than the FPIs after technological innovations (2016 onwards). The empirical analysis suggests that purchase bahaviour of both type of investors is highly attracted by market return. The sale behaviour is sensitive towards both macroeconomic shocks and return in the market. When the purchase of FPIs is higher, then sale of DIIs is higher and the positive of impact of purchase of FPIs is nullifying the negative impact of the DIIs. The GARCH model result suggests that the market return has provided stability to the institutional investment while shocks have generated volatility in the institutional investment of both foreign and domestic in the Indian stock market.